REPRESENTASI PELAKU DAN KORBAN DALAM BERITA PEMERKOSAAN DI MEDIA DARING: ANALISIS WACANA KRITIS - Mayasari Mayasari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Singaperbangsa Karawang, 2017)
Abstract This study describes social representations contained in eonline news media detik.com about rape. This research uses critical discourse analysis Theovan Leuweun model swith the use ofa two-dimensional model ofsocial representations(micro andmacro) and coupled model of textual analysis of Teun van Dijk. Descriptionofthe studyconsisted ofthreemain points, namely(1) the representationof ocialactorsinvolvedinthestudyextualdiscoursebas ed(micro), (2) representation ofthe socialsituationin adiscoursebased onsociocultural aspects(macro), and(3) the relationshipbetweensocialactorsandsocialsituation ofdiscourse.